Accelerated learning model with prezi-assisted concept mapping to teach â€œMovement Systemâ€ - Nurbadriah Nurbadriah; Sri Wardhani; Lia Auliandari (JURNAL BIOEDUKATIKA, 2019)
An accelerated learning model contained practical methods that can be used to accelerate students mastery and understanding of learning materials. This study aimed to investigate the effect of Accelerated Learning model with Prezi-assisted concept mapping on the eight-grade students ability to understand Movement System. This study employed a quasi-experimental pretest-posttest control group design and a cluster random sampling technique to select the sample. It involved students from class VIII.2 (control class) and class VIII.3 (experimental class) of SMP Negeri 3 Sekayu. The result of the t-test analysis showed that the Accelerated Learning model with Prezi-assisted concept mapping had an effect on the students cognitive achievement (significance level of 0.000 < ±/2 (0.025)). The students achievement in affective (honesty and discipline) and psychomotor (creativity in creating a mind map) domains was observed and analyzed during the learning process, then presented in percentage form. The result of the analysis indicated that the experimental class achieved better than the control class in affective and psychomotor domains. The experimental students affective and psychomotor scores were directly proportional to their cognitive achievement. Thus, it can be concluded that the Accelerated Learning Model with Prezi-assisted concept mapping has an effect on the eight-grade students achievement in cognitive, affective, and psychomotor domains, especially in Motion System lesson.